The distribution of (234U/238U) activity ratios in river sediments. (1st December 2020) - Thollon, Maude; Bayon, Germain; Toucanne, Samuel; Trinquier, Anne; Germain, Yoan; Dosseto, Anthony
Abstract: Uranium (U) isotopes can be used to estimate the comminution age of sediments, i.e. the time elapsed from sediment production on continents, via weathering and physical erosion, to deposition in the sedimentary record. The calculation of this comminution age is based on measured ( 234 U/ 238 U) activity ratios in river sediments, and inferred time-dependent recoil effect, which leads to the preferential release of 234 U from mineral lattices during erosion processes. In this study, we report on a large-scale ( 234 U/ 238 U) investigation of modern river sediments worldwide, with the aim to determine the extent to which parameters such as grain size, lithology, weathering, climate and geomorphology may influence the distribution of U isotopes in fine-grained sediments. Our extensive dataset (N = 64) includes U isotopic measurements for many of the world's largest rivers, but also rivers draining particular climatic and geological settings. Our results indicate that sediments collected from river basins draining mostly igneous, metamorphic or volcanic rocks often display ( 234 U/ 238 U) ratios > 1, with clay-size fractions (<4 µm) being less depleted in 234 U (higher 234 U/ 238 U) than corresponding silt-size fractions (4–63 µm). In contrast, sediments derived from multi-lithological basins or draining sedimentary rocks are typically characterized by ( 234 U/ 238 U) ratios <1, with clays generally exhibiting more depleted 234 U signatures than silts. Taken together, these observations suggest that the formation of secondary clay minerals in soils from basins draining mostly igneous, metamorphic is accompanied by partial incorporation by recoil injection of 234 U initially released during weathering processes, possibly from U-rich minerals, such as sphene or apatite. Instead, in multi-lithological catchments draining sedimentary rocks, we propose that the erosion of recycled sediments having experienced several cycles of weathering, possibly over glacial-interglacial timescales, could explain the much lower ( 234 U/ 238 U) ratios observed in clay-size fractions. While no direct relationships can be identified between sediment ( 234 U/ 238 U) ratios and lithology, weathering intensity, climatic or geomorphic parameters in corresponding river basins, we show that the catchment size probably plays an important role in controlling the distribution of ( 234 U/ 238 U) in river sediments, through its direct influence on the sediment residence time. Finally, a multiple regression analysis of our data, combining various environmental parameters for the lithology, climate and geomorphology of studied river basins, indicates predicted ( 234 U/ 238 U) values that are very similar to measured values (with R 2  ∼ 0.8). This finding provides further support for the usefulness of ( 234 U/ 238 U) ratios in the sedimentary record for reconstructing past landscape changes and their effect on sediment transport and residence time in river basins.